Analysis of The Implementation of MSME Tax Calculations Based On The Tax Harmonization Law Number 7 of 2021 In The Bogor Region - Dariansyah, Deddy; Meirinaldi, Meirinaldi; Astuty, Pudji (Green Publisher Indonesia, 2023)
With the enactment of the Law on the Harmonization of Tax Regulations number 7 of 2021, implemented based on the principles of justice, legal certainty, simplicity, efficiency, and national interest, there are several provisions that have an impact on MSME taxpayers, including the imposition of layers of income tax rates (PPH). and changes in non-taxable income, for taxpayers that do not exceed a gross income of Rp. 500,000,000 per year, while taxpayers who exceed gross income of Rp. 500,000,000 to Rp. 4,800,000,000 per year are subject to a 0.5% rate based on PP 23 of 2018 This study discusses the calculation of MSME Taxes with gross income for taxpayers having business in the MSME sector. The method used in this research is qualitative with observations and interviews by analyzing the financial statements of MSMEs and the application of gross Final Income Tax on income from certain business circulations for MSME taxpayers who are food and beverage distributors in 2021, in accordance with Law number 7 of 2021 subject to tariffs Final PPH every month for the efforts of the taxpayer on certain business income